Thiazolidinediones lower the risk of pneumonia in patients with type 2 diabetes - Yen, Fu-Shun; Wei, James Cheng-Chung; Hung, Yu-Tung; Hsu, Chung Y.; Hwu, Chii-Min; Hsu, Chih-Cheng (Frontiers in Microbiology, 2023)
We conducted this study to compare the risk of pneumonia between thiazolidinedione (TZD) use and nonuse in persons with type 2 diabetes (T2D). We identified 46763 propensity-score matched TZD users and nonusers from Taiwan’s National Health Insurance Research Database between January 1, 2000, and December 31, 2017. The Cox proportional hazards models were used for comparing the risk of morbidity and mortality associated with pneumonias. Compared with the nonuse of TZDs, the adjusted hazard ratios (95% CI) for TZD use in hospitalization for all-cause pneumonia, bacterial pneumonia, invasive mechanical ventilation, and death due to pneumonia were 0.92 (0.88-0.95), 0.95 (0.91-0.99), 0.80 (0.77-0.83), and 0.73 (0.64-0.82), respectively. The subgroup analysis revealed that pioglitazone, not rosiglitazone, was associated with a significantly lower risk of hospitalization for all-cause pneumonia [0.85 (0.82-0.89)]. Longer cumulative duration and higher cumulative dose of pioglitazone were associated with further lower adjusted hazard ratios in these outcomes compared to no-use of TZDs. This cohort study demonstrated that TZD use was associated with significantly lower risks of hospitalization for pneumonia, invasive mechanical ventilation, and death due to pneumonia in patients with T2D. Higher cumulative duration and dose of pioglitazone were associated with a further lower risk of outcomes.